A novel and reusable magnetic nanocatalyst developed based on graphene oxide incorporated strontium nanoparticles for the facial synthesis of β‐enamino ketones under solvent‐free conditions. (22nd October 2018) - Mousavi, Seyyed Rasul; Sereshti, Hassan; Rashidi Nodeh, Hamid; Foroumadi, Alireza
Abstract : A novel magnetic SrFeGO nanocatalyst (NC) was synthesized through a simple sol–gel technique by introducing strontium and iron oxide nanoparticles onto graphene. The synthesized NC was characterized using FT‐IR and FE‐SEM. Subsequently, the catalytic activity of SrFeGO was tested in a reaction between β‐dicarbonyl compounds and aniline derivatives to gain β‐enamino ketone derivatives under solvent‐free conditions. It was found that SrFeGO NC is a potential catalyst for the synthesis of β‐enamino ketones. The β‐enamino ketone produced by such reactions could be isolated in high purity without the need for chromatographic purifications. The newly prepared magnetic graphene oxide nanocomposite could be recovered and reused for numerous times with no significant decrease in efficiency. Moreover, the protocol has the advantages of excellent yielding (up to 98%) in short a reaction time, benefitting an easy workup procedure and being environmentally friendly. Abstract : A novel magnetic SrFeGO nanocatalyst (NC) was successfully prepared through a simple sol–gel technique by introducing strontium and iron oxide nanoparticles onto graphene. The as prepared nanocatalyst was well characterized and found to be highly efficient heterogeneous catalyst for the synthesis of β‐enamino ketones under sustainable conditions (solvent‐free at 110 °C in short reaction time). Furthermore, the newly synthesized magnetic graphene oxide nanocomposite could be simply recovered and reused for numerous times without substantial decrease in its catalytic activity.